Piper sarmentosum leaf as a promising non-toxic antiparasitic agent against trypanosoma evansi-induced mice - Baba, Mohd Shukri; Abu Hassan, Zainal Abidin (Microscopy Society of Malaysia, 2019)
Realizing that Trypanosoma evansi is now has been potentially trans-infected to human from animals, this study demonstrated how the manipulation of natural plant, Piper sarmentosum, promisingly can solve the endemicity of vector-borne zoonotic manifestation of atypical human trypanosomiasis (AHT) and Surra disease in livestock. Groups of male mice were intraperitoneally administered with the parasite at 5.0 × 103 T. evansi/mouse and orally given pre-and post-infection treatments with 0.2 mL of 10 mg/mL of P. sarmentosum-dH2O extract per mouse. By using Giemsa stained blood smear, the development of parasite cells, toxicity level of mice blood enzymes, histopathology of selected organs and survival rate of the mice were investigated. The morphological changes of T. evansi cells were evidenced and a positive correlation (p ≤ 0.05, n = 6) were recorded between the mice survival time and the ability to inhibit the parasites growth in pre-infection treatment group, PRE14. Besides, PRE14 group was also recorded the longest pre-patent and survival period. The mice blood enzymes were significantly situated in the normal ranged and no abnormalities were found on the selected organs. This study evidenced that P. sarmentosum could be manipulated as a potential antiparasitic alternative drug towards trypanosomiasis. © Malaysian Journal of Microscopy (2018). All rights reserved.